AN OVERVIEW OF JAPAN-INDONESIA MARITIME SECURITY OF INDO PASIFIC REGION - Nurjannah, Siti; Ardiyanti, Dwi; Abdallah, Kajoba Abdul Rahim; Mubarak, Sofi (Indonesian Journal of International Relations, 2025)
The Indo-Pacific region has become the center of targetted market in global partnership. Due to its strategic economic, political and security aspects, there is a need to maintain the securities along the side of Pasific ocean. Indonesia and Japan's foreign policies focuses on building global market access, in which results in impact for regional stability and security toward neighbouring countries of Indo Pasfic. Meanwhile, consideration on how Japan and Indonesia maintain the good partnership between both by Meanwhile, we are considering how Japan and Indonesia maintain a good partnership between the two through the Indonesia-Japan Maritime Forum (IJMF). The scope of cooperation includes the fields of maritime security and maritime safety, maritime economic development, maritime infrastructure development and maritime education and training. This research presents innovation by combining analysis of regional scuroty complex based on the national interests of two countries. The research uses a text-based qualitative descriptive method with a descriptive-interpretive analysis approach. This approach allows researchers to understand and explain the comparative maritime defense policies of the two countries from the perspective of national interests. The Indo-Pacific region is becoming increasingly important in world security politics, with Indonesia and Japan as two key players who prioritize their national interests. The synergy between these two countries is the key to creating better stability and security in this region. The research question posed in this article is what is the picture of Indonesia and Japan's maritime foreign policy regarding the Indo-Pacific region and its implications for regional security stability.